Eradicating poverty and hunger, providing health services and quality education through Islamic social finance: Qatar as a model - Al Marri, Mohamed Saleh; Awang Hamat, Mohd. Afandi; Mohamed, Hossam El-Din Ibrahim; Zakariyah, Habeebullah (Al-Hikmah Research & Publication Centre, 2022)
This paper aimed to address four important goals of the sustainable development goals, which are the eradication of poverty and hunger, the provision of health services and quality education. It also signifies the importance of Islamic social finance and its potential in achieving these goals with different examples in Qatar. The inductive approach was relied on, and the study showed that the efforts of Qatar to eradicate poverty and hunger since the past decade have borne fruit through the cooperation of all sectors and several policies and institutions that included Islamic social finance institutions, and that Islamic financial institutions actively participate in efforts to provide health services. This paper also found that Qatar provides quality education to all citizens with the aim of building generations aware of a culture of peace ،and the country's government is also promoting means of benefiting from science and technology. However, Islamic social finance institutions still need to expand the horizons of their support for education and health services through the dissemination of public knowledge on tools such as Sukuk (Islamic bonds), in addition to the fact that challenges still exist regarding the implementation of some national policies to achieve integration between different sectors and Islamic social finance institutions.